Silver nanowire transparent conductors for quantum dot photovoltaics - Hjerrild, N; Natasha E. Hjerrild (2013)
This thesis studies the application of silver nanowire transparent conductors in PbS quantum dot photovoltaics. Silver nanowires were synthesized using a colloidal method and characterized using scanning electron microscopy. Nanowires were deposited on glass substrates by a stamp transfer process to generate a low density continuous network of conductive nanowires. This resulted in a highly conductive and transparent film appropriate for optoelectronic applications. Nanowire synthesis, deposition, and processing were optimised to produce transparent conductors suitable for thin film photovoltaics. These nanowire films were used to fabricate lead sulphide (PbS) colloidal quantum dot solar cells. In this structure, p-type PbS quantum dots form a junction with a n-type ZnO nanoparticle layer. A variety of fabrication and processing treatments were developed in order to reduce short-circuiting of devices and to enhance cell performance. Moderate nanowire density, improved ZnO adherence, slight device aging, and increased PbS film thickness proved to result in the highest quality devices. The champion device developed in this thesis achieved a power conversion efficiency of 2.2%.